Comparing Sex Offender Risk Assessment Measures on a UK Sample - Craig, Leam A. (International journal of offender therapy and comparative criminology, 2004)
The purpose of this study on 139 sex offenders was to consider the application of six measures of risk: Static-99, SACJ-Min (Structured Anchored Clinical Judgment Scale-Minimum), RRASOR (Rapid Risk Assessment for Sexual Offence Recidivism), Risk Matrix 2000-Sexual/Violent, and SVR-20 (Sexual Violence Risk-20) and to compare risk assessments conducted by a Regional Secure Unit (RSU) and the Probation Service. Levels of risk for the RSU sample ranged from1% to 42% low risk to1% to 66% high risk compared with the Probation sample of 8% to 43% low risk to 4% to 70% high risk. Offenders with adult victims obtained significantly higher scores using the RM2000/S and SACJ-Min than did those with child victims who obtained significantly higher scores on the RRASOR. Sex offenders referred to a RSU scored significantly higher on RRASOR and RM2000/S than did sex offenders supervised by the Probation Service. Forensic practitioners may be better served if risk measures assess specific subcategories of sexual offenders